PREDICTION OF THE DEVELOPMENT OF GROUNDWATER QUALITY IN A FINISHED SLUDGE LAGOON - Petr Černoch; Jiří Košťál (Acta Polytechnica CTU Proceedings, 2018)
This study deals with prediction of the development of groundwater quality in a finished sludge lagoon. For depositing and predicting secondary float energy by-products, it is appropriate to use mathematical modelling. The implementation of relevant input data from long-term monitoring is suitable as an application for verification as well. The main output was the determination of the necessary priorities and geotechnical risks in solving the final state of the area of interest, especially regarding solving of the drainage system in the subsequently finished sludge lagoon.